SOCIAL CAPITAL IN KERALA: MIXED EVIDENCE FROM A VILLAGE PANCHAYAT - Jos Chathukulam and M.S. John (The Indian Journal of Political Science, 2003)
This paper is based on a micro-study of social capital in a in Kerala. It argues that the predominant village Panchayat characteristic of much of the associational life that came into with entitlements rather being is based on a pre-occupation than commitment to collective action of a civic kind. It also out the limitations of social capital points generated through the inter within a framework of mediation of political parties forms to be streamlined into more positive of civic agitation The idea of synergistic action did not materialize engagement. the period of participatory in the Panchayat. during planning It was also found that social capital was strongest in those of the study where political were regions Panchayat parties exist. weak and non-political horizontal relatively organizations